Model Tarian Kreatif Dalam Pelajaran Seni Tari Pada Pelajar PGSD Univeritas Negeri Surabaya - Arifin, Mohammad Syamsul; Yanuartuti, Setyo (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
This study describes a creative dance model in dance lessons for PGSD students at the State University of Surabaya. The purpose of this research is to find out the making of dance for elementary school children, making elementary school children's dances through creative dance models, the process of making dance creations, developing an idea and being creative, as well as having the objective of analyzing creative dance models to create children's dances. Elementary school children in dance lessons. The creative dance model means a creative dance model. The research method uses qualitative research and descriptive analysis. Data collected from documentation, observations, and observations. The results of this study are the product of a lesson model for coaching guidelines and dance exploration for children for PGSD students at the State University of Surabaya.